Low intensity ultrasound mediated liposomal doxorubicin delivery using polymer microbubbles - Yu, Francois T.H. (Mol Pharm, 2015)
Cardiotoxicity is the major dose-limiting factor in the chemotherapeutic use of doxorubicin (Dox). A delivery vehicle that can be triggered to release its payload in the tumoral microvasculature but not in healthy tissue would help improve the therapeutic window of the drug. Delivery strategies combining liposomal encapsulated Dox (LDox), microbubbles (MB) and ultrasound (US) have been shown to improve therapeutic efficacy of LDox but much remains to be known about the mechanisms and the US conditions that maximize cytotoxicity using this approach. In this study, we compared different US pulses in terms of drug release and acute toxicity. Drug uptake and proliferation rates using low intensity US were measured in squamous cell carcinoma cells exposed to LDox conjugated to or co-injected with polymer MB. The aims of this study were: (1) to compare the effects of low and high pressure US on Dox release kinetics; (2) to evaluate whether conjugating the liposome to the MB surface (DoxLPX) is an important factor for drug release and cytotoxicity; (3) to determine which US parameters most inhibits cell proliferation, and whether this inhibition is mediated by drug release or the MB/US interaction with cells. Low pressure US (170 kPa) at high duty cycle (stable cavitation) released up to ~70% of the encapsulated Dox from the DoxLPX, thus improving Dox bioavailability and cellular uptake and leading to a significant reduction in cell proliferation at 48 h. Flow cytometry showed that US generating stable oscillations of DoxLPX significantly increased cellular Dox uptake at 4 h after US exposure compared to LDox. Drug uptake was correlated with cytotoxicity at 48 h. Our results demonstrate that Dox-containing liposomes conjugated to polymer MB can be triggered to release ~70% of their payload using non-inertial US. Following release, Dox became bioavailable to the cells and induced significantly higher cytotoxicity compared to non-released encapsulated drug. Our findings show promise for targeted drug delivery using this theranostic delivery platform at low US intensities.